Analysis of Quality Enhancement of the Government Financial Statements of West Sulawesi Province - Petrus Peleng Roreng (International Journal of Advanced Science and Technology, 2020)
This study aims to analyze the improvement of the quality of the financial statements of the Regional Government of West Sulawesi Province through the competence of Human Resources and Internal Control Systems. This study uses a qualitative approach to the stages of data collection, data reduction, data display, verification and conclusion drawing.